2012
DOI: 10.4103/0301-4738.100548
|View full text |Cite
|
Sign up to set email alerts
|

Eye conditions and blindness in children: Priorities for research, programs, and policy with a focus on childhood cataract

Abstract: The major causes of blindness in children encompass intrauterine and acquired infectious diseases, teratogens and developmental and molecular genetics, nutritional factors, the consequences of preterm birth, and tumors. A multidisciplinary approach is therefore needed. In terms of the major avoidable causes (i.e., those that can be prevented or treated) the available evidence shows that these vary in importance from country to country, as well as over time. This is because the underlying causes closely reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Our review explored how school-based eye-care services function and connect with general health systems, how stakeholders interact with school-based eye-care services and programmes, and the possible paths to meeting population needs in a way that is equitable and responsive 70 , 71 . School-based eye-care interventions (including vision screenings) are key to reducing morbidity and developmental delays associated with vision impairment, while promoting early detection and prevention of eye diseases 67 , 72 . Increasing the availability of school-based eye-care interventions in low- and middle-income countries can help to address the burden on poorly resourced secondary and tertiary eye-care, 73 , 74 and enhance access for underserved rural children 21 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Our review explored how school-based eye-care services function and connect with general health systems, how stakeholders interact with school-based eye-care services and programmes, and the possible paths to meeting population needs in a way that is equitable and responsive 70 , 71 . School-based eye-care interventions (including vision screenings) are key to reducing morbidity and developmental delays associated with vision impairment, while promoting early detection and prevention of eye diseases 67 , 72 . Increasing the availability of school-based eye-care interventions in low- and middle-income countries can help to address the burden on poorly resourced secondary and tertiary eye-care, 73 , 74 and enhance access for underserved rural children 21 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…It could also be that males are at greater risk of blinding conditions than females or blind females have a higher mortality rate than blind males or the parents of blind males are more willing to seek eye care than the parents of blind females. Gilbert et al, [4] reported in their study that families less readily perceive a girl to be ill than a boy, and so health care is not sought. This may, in part, explain why virtually all studies in developing countries report higher prevalence of childhood blindness in males than females.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the findings reported could be due to rapid and marked socioeconomic changes in different countries. Moreover, studies have shown that as the economies of most countries continue to improve, the major causes of childhood blindness will also continue to change; retinal disorder will likely become a major cause of childhood blindness in developing countries while cataract will continue to overtake corneal scarring as the major avoidable cause in poor countries in Africa such as Nigeria [4]. Emphasis therefore needs to be placed on initiatives and programs for the control of blindness from retinal disorder and cataract in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy for childhood blindness should comprise elements such as sustained political commitment (promoting eye health as part of the national health policy); active collaboration from all stakeholders, government/private, and civil society; adoption of appropriate technology (to ensure that greatest benefit accrues to largest number of people, within the limited resources available); strengthening of human resources/infrastructure; operational research to determine capacity of existing infrastructure/level of utilization and barriers to utilization; [6] institutional capacity building for enhancing training of ophthalmologists and allied health personnel for eye care including pediatric eye care; resource mobilization; advocacy of community-based rehabilitation services; epidemiologic assessments and priority setting on the basis of evidence-based public health approach; coordinating primary prevention of vitamin A deficiency/rubella cataract with nutrition and immunization programs; collaboration-cooperation and coordination at the regional/national and international levels with nongovernment organizations; and finally building proper mechanisms for monitoring…”
Section: Childhood Blindness: Is My World Getting Smaller?mentioning
confidence: 99%